Anatomical resections for pulmonary metastases: a narrative review of indications, techniques, and outcomes - Campisi, Alessio; Dell'Amore, Andrea (Cancers, 2025)
Background: Pulmonary metastases occur in approximately 20–40% of patients with solid malignancies, with colorectal cancer representing the most frequent primary source. Surgical resection remains a potentially curative strategy for selected patients, and wedge metastasectomy has long been considered the standard of care. However, increasing attention has been paid to the role of anatomical resections such as segmentectomy and lobectomy, particularly for centrally located or technically challenging metastases. Methods: We performed a narrative literature review across PubMed, Embase, and Scopus databases covering the period 2010–2025, using the keywords “pulmonary metastasectomy”, “anatomical resection”, “segmentectomy”, “lobectomy”, and “pneumonectomy”. Articles included original series, comparative studies, meta-analyses, and systematic reviews. Special attention was given to technical indications, oncological outcomes, minimally invasive techniques, histological differences, and postoperative functional results. Results: Evidence suggests that anatomical resections are most often indicated not purely on oncological grounds, but due to technical considerations such as central localization, size greater than 2 cm, involvement of segmental or lobar bronchi or vessels, or the presence of multiple metastases confined to one lobe. Comparative studies indicate that segmentectomy provides superior local control compared to wedge resection, while lobectomy ensures complete clearance in complex cases, with five-year overall survival approaching 50% in carefully selected colorectal cancer patients. Conclusions: While wedge resection and metastasectomies remain the gold standard for small, peripheral metastases, anatomical resections represent a valuable extension of the surgical armamentarium in secondary lung cancer. Their role should be understood primarily as a technical necessity to ensure radical clearance while minimizing loss of lung parenchyma. The integration of minimally invasive approaches and emerging adjuncts, such as 3D reconstruction and fluorescence-guided surgery, is likely to further refine patient selection and optimize outcomes.